Efficient carrier frequency offset estimation algorithm for generalized frequency division multiplexing systems - Wang, Yung-Yi; Yang, Shih-Jen; Lin, Ting-Chieh (Signal processing, 2020)
This paper presents an efficient carrier frequency offset (CFO) estimation algorithm for generalized frequency division multiplexing (GFDM) systems. The proposed algorithm formats the preamble into multiple identical subsymbols, and then decimates the received signal in the time domain to estimate the fractional CFO through array signal processing. After compensating for the fractional CFO, the proposed algorithm uses a low-complexity searching process to estimate the integer CFO in a maximum likelihood. The proposed algorithm presents some distinctive features: (1) it provides the full range of frequency acquisition region (FAR), which was considerably larger than that provided by many existing algorithms whose FAR was limited to one subcarrier spacing; (2) the proposed algorithm can use a single subsymbol to estimate the integer CFO by using the searching process of stepsize 1, significantly reducing its computational complexity; and (3) the decimation of the received signal ensures the proposed algorithm a power gain in fractional CFO estimation, resulting in an improved estimation accuracy compared with conventional algorithms.